A progress report of the project to develop a vaccine against avian tuberculosis in wildfowl - Cromie, Ruth L; Stanford, John L; Brown, Martin J; Price, David J (Wildfowl, 1989)
Techniques for monitoring the efficiency of an anti-tuberculosis vaccine for wildfowl have been developed. These include web testing lymphocyte transforation test (LTT) and an enzyme linked immunosorbance assay (ELISA). Using these methods a number of trial vaccines have been assessed with a fair degree of success. A vaccine has been found that gives increased LTT and web test responses and will, we hope, therefore increase protection from infection. An optimum dose of this potential vaccine has been found and this should be administered to day-old birds.